2023
DOI: 10.1002/iid3.834
|View full text |Cite
|
Sign up to set email alerts
|

The validation of artificial anti‐monkeypox antibodies by in silico and experimental approaches

Abstract: As a result of smallpox immunization programs that ended more than 40 years ago, a significant portion of the world's population is not immune. Moreover, due to the lack of anti‐monkeypox drugs and vaccines against monkeypox, the spread of this virus may be the beginning of another challenge. In this study, novel antibodies against monkeypox virus were modeled based on a heavy chain of human antibody and a small peptide fragment. Docking of modeled antibodies with C19L protein showed the range of docking energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The interaction between the C19L protein and the synthetic and wild-type anti-C19L antibodies was analyzed using SPR. The findings showed that synthetic antibodies’ K D value was lower than wild antibodies, 0.1 and 0.8 nM, respectively, meaning that synthetic antibodies had a higher affinity for MPXV C19L protein ( Shabani et al., 2023 ). In this manner, SPR enabled a label-free, direct, and real-time quantitative assessment of molecular interactions ( Shi et al., 2022 ).…”
Section: Rapid Detection Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…The interaction between the C19L protein and the synthetic and wild-type anti-C19L antibodies was analyzed using SPR. The findings showed that synthetic antibodies’ K D value was lower than wild antibodies, 0.1 and 0.8 nM, respectively, meaning that synthetic antibodies had a higher affinity for MPXV C19L protein ( Shabani et al., 2023 ). In this manner, SPR enabled a label-free, direct, and real-time quantitative assessment of molecular interactions ( Shi et al., 2022 ).…”
Section: Rapid Detection Techniquesmentioning
confidence: 97%
“…Likewise, the same study employed SPR to study the affinity of the MPXV L1R protein to GAG. Shabani et al (2023) designed a new synthetic anti-MPXV C19L antibody (antibody 62) based on a heavy chain of human antibodies and a small peptide fragment at its beginning. The docking and molecular simulation analysis of the designed anti-MPXV C19L antibodies were applied to select the one with superior stability.…”
Section: Rapid Detection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation